Determinants of Foreign Direct Investment in India - Penn, Rebecca (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The main aim of this thesis is to analyze the determinants of foreign direct investment in India by using GDP, Inflation, Economy Openness and Real Effective Exchange rate as determining variables. This study uses time series data from 1978 to 2014. The unit root test revealed that the variables were stationary at first level I(1). The variables were found to be co-integrated after conducting the Johanson’s Co-integration text. In order to determine the long run coefficients of the variables, we used the Vector Error Correction Model (VECM) that produced the following results. GDP was found to be positive and statistically significant variable exhibiting a positive relationship between FDI and GDP. The VECM reveals exchange rate as a significant determinant of FDI in India. This indicates that the strength of India’s currency is a measure factor in attracting FDI to India. The results of this study also provide evidence that inflation is negatively related to FDI in the long run probably because of the instability it causes in the economy. Trade openness is negative and statistically significant indicating a negative relationship with FDI probably because investors coming in are market seeking oriented and not export oriented. Also, trade openness may increase the number of competitors in the domestic market. Keywords: Foreign Direct Investment, Unit root test, Johanson Co-integration, VECM and India.

Öz: Bu tezin temel amacı Hindistan'a yapılan doğrudan yabancı yatırımın (DDY) belirleyicilerini belirleme ve değişkenleri olarak GSYİH, Enflasyon, Ekonomik Açıklık ve Gerçek Etkili Kur kullanarak analiz etmektir. Bu çalışma, 1978-2014 yılları arasındaki zaman serileri verilerini kullanmaktadır. Birim kök testi, değişkenlerin birinci basamak I'de sabit olduğunu ortaya koymaktadır (1). Değişkenlerin, Johanson'un Eş Bütünleştirme metnini uyguladıktan sonra birlikte entegre oldukları bulundu. Değişkenlerin uzun dönem katsayılarını saptamak için aşağıdaki sonuçları üreten VECM (Vector Error Correction Model) kullanılmıştır. GSYİH'nin pozitif olduğu ve DDY ile GSYİH arasında pozitif bir ilişki sergileyen istatistiksel olarak anlamlı değişken olduğu tespit edildi. VECM, döviz kurunu Hindistan'da doğrudan yabancı yatırımın önemli bir belirleyicisi olarak ortaya koyuyor. Bu, Hindistan'ın para biriminin gücünün Hindistan'a doğrudan yabancı yatırım çekme ölçütü olduğuna işaret ediyor. Bu çalışmanın sonuçları, enflasyonun muhtemelen ekonomide ortaya çıkardığı istikrarsızlık nedeniyle uzun vadede DYY ile negatif ilişkili olduğuna dair kanıt sağlamaktadır. Ticaretin açıklığı olumsuzdur ve istatistiksel olarak anlamlıdır, muhtemelen DYY ile negatif bir ilişki gösterir çünkü gelen yatırımcılar pazar odaklıdır ve ihracat odaklı değildir. Ayrıca, ticaretin açık olması iç pazardaki rakip sayısını artırabilir. Anahtar Kelimeler Doğrudan Yabancı Yatırım, Birim Kök Testi, Johanson Eşentegrasyonu, VECM ve Hindistan.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Assoc. Prof. Dr. Melek Şule Aker.
Keywords: Business Administration; Marketing Management; Investments; Foreign; India; Foreign Direct Investment; Unit Root Test; Johanson Co-Integration; VECM and India